SURKHAN OASIS IN B.H. KARMISHEVA’S RESEARCH ETHNIC DESCRIPTION OF “YUZ” TRIBES - Turaev, Sherzod (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
The article provides an example of a study by the ethnographer, Turkologist B. Kh. Karmisheva on ethnic education, division, location and ethnic history of the person in the Surkhandarya oasis. The Uzbek people are considered ethnically diverse, and in the Surkhandarya oasis, known as an ethnographic region, the Yuz tribe had a great influence. In particular, it was revealed that a hundred seeds were played an important role in the social life of the Surkhandarya oasis at the beginning of the 19th-20th centuries, distribution areas, the composition of hundreds of seeds, and their close connection with the Surkhandarya people.